The Determinant Factors of Rice’s Marketed Surplus in Bone Bolango Regency - Yuliana Bakari (Journal of International Conference Proceedings (JICP), 2018)
The small holder farmers and farm land size ownership are problems that have an effect to farmer’s rice production and be a part to determine a marketing producer’s surplus. Particularly, marketed surplus is the grand theory of producer’s surplus which is explained in this research. The purpose of this study is to examine and analyze the determinant factors of rice marketed surplus in Bone Bolango regency. The study was conducted purposively in Bone Bolango regency with stratified sampling technique as sampling collected method. Multiple Regression Analysis with BLUE (Best Linear Unbiased Estimator) are used as data analysis method. The results showed that rice’s marketed surplus and off-farm income are significant and positive determine rice’s marketed surplus whereas the farmer loan has significant affect within negative sign. Nevertheless, farm size, Number of family members and consumption has not significant effect to rice’s marketed surplus in Bone Bolango regency. Keywords: marketed surplus, producer’s surplus, rice marketing, rice’s marketed surplus